A Comparative Study of Non-Execution Auction Implementation Mechanisms in Indonesia and the Philippines - Maskanah, Ummi; Rosmiati, Rina; Hidayati, Tara Devilia; Rahmawati, Suci (Manunggal Halim Jaya, 2025)
This study aims to analyse the comparison of regulations, procedures, and legal protection in the implementation of non-execution auctions in Indonesia and the Philippines through a legal-normative approach. This study uses a normative legal research method with a statute approach and a comparative approach. In Indonesia, non-execution auctions are a state administrative mechanism under the authority of the State Property and Auction Service Office (KPKNL) as regulated in Minister of Finance Regulation No. 122 of 2023, which emphasises formal legal certainty and procedural legality as a means of legal and transparent transfer of rights. Meanwhile, in the Philippines, the extrajudicial foreclosure mechanism regulated in Act No. 3135 jo. Act No. 4118 gives creditors direct authority to execute collateral without a court order, while still guaranteeing the substantive rights of debtors through the principle of equitable redemption and the redemption period. The comparison shows that the Indonesian system is oriented towards administrative efficiency and formal legal certainty, while the Philippines emphasises corrective justice and the protection of civil rights. This difference in orientation illustrates two complementary legal approaches legal certainty according to Gustav Radbruch and corrective justice according to Aristotle which, if integrated, could give rise to an ideal non-execution auction model: economically efficient, substantively fair, and legally accountable. This research is expected to provide a conceptual contribution to the development of a more adaptive and equitable non-execution auction legal system in Indonesia and the Southeast Asian region.